The Use of Two Stay Two Stray Strategy to Improve Students Writing Ability in Report Text - Ita Fatmawati (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2019)
Two stay two stray strategy is a fun learning activity because the strategy makes students motivated in learning to write report text. This research uses classroom action research to solve some problems at class IX SMP Al-muhajirin somengko in learning to write English. The problems are less interested in writing English, lack of ideas, grammar, and lack vocabulary. Based on the problems the writer tried to conduct classroom action research by applying two stay two stray strategy. The purpose of this research are: (1) To describe the implementation of two stay two stray strategy in teaching writing for nine grade students of SMP Al-Muhajirin Sumengko. (2) To describe the improvement of writing ability of nine grade students of SMP Al-Muhajirin Sumengko after implementing two stay two stray strategy. (3) To describe the student's response to the implementation of two stay two stray strategy. This study was conducted in 1 cycle of two meetings through four stages: planning, action, observation, and reflection. Data collected through observation checklist, field notes, and questionnaires. The result from data analysis found that students' ability improved after post-activity assignment. The evident isÂ from the results of tests showing the pre-activity assignment data is 13.6 with the category of students adequate to fair, after post activity assignment is 15.7 with category student ability good to adequate. It can be concluded that two stay two stray strategy is successfully implemented to improve the ability to write students.